Low Levels of Granulocytic Myeloid-Derived Suppressor Cells May Be a Good Marker of Survival in the Follow-Up of Patients With Severe COVID-19 - Jiménez-Cortegana, Carlos; Sánchez-Jiménez, Flora; Pérez-Pérez, Antonio; Álvarez, Nerissa; Sousa, Alberto; Cantón-Bulnes, Luisa; Vilariño-García, Teresa; Fuentes, Sandra; Martín, Salomón; Jiménez, Marta; León-Justel, Antonio; de la Cruz-Merino, Luis; et al. (Frontiers in Immunology, 2022)
SARS-CoV2 infection cause a disease (COVID-19) that may develop a systemic disease with immunosuppression and death in severe forms of COVID-19. Myeloid derived suppressive cells (MDSCs) are inhibitory cells that contribute to the immunosuppression in patients with cancer and infection. Increased levels of MDSCs have been found in COVID-19 patients although their role in the pathogenesis of severe COVID-19 has not been clarified. That is why we raised the question whether MDSCs could be useful in the follow-up of patients with severe COVID-19 in the intensive care unit (ICU). Thus, we monitored the immunological cells, including MDSCs, in 80 patients at admission in ICU, and after 1, 2 and 3 weeks to look for the possible association with mortality (40 patients). Even though the basal level of circulating MDSC did not discriminate between both groups, the last measurement before the endpoint (death or ICU discharge) showed that patients discharged alive from the ICU had lower levels of granulocytic MDSCs (G-MDSCs), higher level of activated lymphocytes and lower level of exhausted lymphocytes, compared with patients with bad evolution (death). In conclusion, a steady increase of G-MDSCs during the follow-up of patients with severe COVID-19 was found in those who finally die.